2018
DOI: 10.1039/c8ra01745j
|View full text |Cite
|
Sign up to set email alerts
|

Extraction in cholinium-based magnetic ionic liquid aqueous two-phase system for the determination of berberine hydrochloride in Rhizoma coptidis

Abstract: Five cholinium type organic magnetic ionic liquids have been applied in ionic liquid-based aqueous two-phase systems by mixing with a series of inorganic salts, which is reported to extract berberine in quantitative analysis for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Then an increase in the amount of ionic liquid causes an increase in the volume of the upper phase and a decrease in the volume of the lower phase. Therefore, the extraction efficiency begins to decrease [24]. The highest recovery was obtained with 200 µL of ionic liquid for three MILs.…”
Section: Volume Of Milmentioning
confidence: 93%
See 1 more Smart Citation
“…Then an increase in the amount of ionic liquid causes an increase in the volume of the upper phase and a decrease in the volume of the lower phase. Therefore, the extraction efficiency begins to decrease [24]. The highest recovery was obtained with 200 µL of ionic liquid for three MILs.…”
Section: Volume Of Milmentioning
confidence: 93%
“…They achieved rapid extraction with MIL and showed that extraction efficiency was enhanced. Nie et al prepared cholinium-based MIL and used ATPE for berberine hydrochloride in Rhizoma coptidis [24]. High extraction efficiency and rapid phase separation were obtained with this MIL.…”
Section: Introductionmentioning
confidence: 99%
“…MILs have found some applications in the plant field, in particular in the extraction of sinomenine from Sinomenium acutum (Thunb.) Rehder & E.H.Wilson [17] and in the extraction, adopting an ABS approach, of berberine from the rhizome of Coptis spp [18]. They also have been used for the isolation of DNA from Arabidopsis thaliana (L.) Heynh.…”
Section: Ionic Liquidsmentioning
confidence: 99%
“…However, due to their high affinity for water, these ILs are usually studied in combination with polyethylene glycol (PEG) or polypropylene glycol (PPG) to form ABS [ 23 , 24 , 25 , 26 , 27 ]. On the other hand, there is only a limited number of reports about choline-based ILs applied to develop ABS with inorganic or organic salts [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%